The implementation of IT strategic planning in healthcare organizations / Ahmad Soufiean Othman, Azmi Ab Rahman and Mohd Nor Azam Salleh - Othman, Ahmad Soufiean; Ab Rahman, Azmi; Salleh, Mohd Nor Azam (Faculty of Information Management, 2015)
The implementation of IT strategic planning in healthcare organization is a good step for the future of healthcare organizations as it provides benefits to help in providing better services and in achieving business goals. Even though there are many challenges in implementing IT strategic planning, the outcomes for such effort to implement IT strategic planning will always gain positive impact towards the healthcare organization. IT manager in healthcare organization should study the process of implementing IT strategic planning to be able to conduct and lead the healthcare organization with more effective solutions regarding its services. IT manager in healthcare organizations must realize the importance of implementing the IT strategic planning to set the IT goals accordingly to the organizations requirement. They have to study the steps, methods and procedure of implementing IT strategic planning to achieve the best result and benefit from the strategic planning. IT strategic planning is important to healthcare organization in ensuring that every objectives of a business is aligned and have good strategies to make sure the outcomes for the business is always more better and provide effective solutions with IT advance tools and technology.